PENYELESAIAN HUKUM TUMPANG TINDIH KEPEMILIKAN TANAH (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 221 PK/PDT.2014) - INDRI HANDAYANI (PREMISE LAW JURNAL, 2017)
One example of a dispute over land title is the case between Peter Soetjipto and Hanan. How about the legal force of the land title with legal standing such as Renunciation Deed made by a Notary, how about the judge’s consideration in pronouncing the case, and whether the settlement of the overlapping land title case has provided legal certainty to the legitimate owner. The legal force of a land title grounded on the Renunciation Certificate made by a Notary proved that there has been a civil title transfer over a land from someone. The judge’s was not grounded on the legal fact in the hearing and merely grounded on the written evidence proposed by the Plaintiff. the settlement of the overlapping land title case has failed to provide legal certainty to the legitimate owner i.e. the Defendant, It is suggested that the Notary, in making a renunciation deed, be more conscientious in verifying the evidence of the land title proposed by the parties the Judge in his consideration to settle the similar dispute case be impartial in verifying the evidence and analyzing the legal facts Keywords: Legal Settlement, Overlapping, Land Title.